„Kötelékek köteléke” Azonosságok Moses Hess és Karl Marx korai filozófiai munkásságában, különös tekintettel a pénz gazdaságfilozófiai értelmezésére - Szücs, Balázs (Hallgatói Műhelytanulmányok, 2022)
Szűcs, Balázs: “The bond of bonds” – Identities in the early philosophical eork of Moses Hess and Karl Marx, with special reference to the economic philosophical interpretation of moneyIn my essay, I attempted to demonstrate the similarities between the two philosophers, Hess and Marx, especially regarding the essence of money. I present the effect of Hess on the young Marx. In the first section of the essay, a short biography of the French Jewish philosopher, Moses Hess is presented and a brief analysis of the most important works of Hess, like European Triarchy (1841), The Philosophy of Action (1843) and Rome and Jerusalem (1862) is given. In these works, there are a number of philosophical categories and definitions that appear in Marx’s works in similar formulation, for instance the determinism of activity, raw possession and the concept of an authority based (Autoritaten) and repressive state, which is the greatest barrier to free self-accomplishment (Selbstbestimmung). But another striking similarity is that Prometheus is regarded, by both philosophers, as the personification of freedom. The second part of the essay provides a detailed analysis of On the Essence of Money (1845). In this work, Hess gives a unique perspective on human history from its beginning to his own age, with many sharp and prophetic philosophical conclusions. Money has entered this system of philosophy, of history as a necessary evil and by staying for too long in the system, it causes alienation. At the end of the study, there is a comparison of the categories and their explanations that can be found in both philosophers’ works. Comparison of On the Essence of Money and Marx’s Economic and Philosophic Manuscripts of 1844, where Hess’s influence on Marx is most evident.